The wild bunch [videorecording (DVD)] - Feldman, Phil, 1922-1991; Peckinpah, Sam, 1925-1984; Green, Walon; Sickner, Roy (Warner Home Video, 2006)
The brutal story of violent men who lived during the Mexican revolution in the year 1913. It portrays a band of magnificent losers in a dying lawless West.